2018
DOI: 10.1177/2325967118811042
|View full text |Cite
|
Sign up to set email alerts
|

Injury Risk and Injury Burden Are Related to Age Group and Peak Height Velocity Among Talented Male Youth Soccer Players

Abstract: Background:The relationship between injury risk (IR) in age groups and periods around peak height velocity (PHV) remains unclear. PHV is defined as the moment of the largest increase in body height.Purpose:To investigate injury risk and injury burden as functions of growth velocity (periods around PHV) and chronological age groupings (under 12 years [U12] to U19) in talented youth male soccer players.Study Design:Cohort study; Level of evidence, 2.Methods:A total of 170 players from the youth academy of a Dutc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
104
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(134 citation statements)
references
References 29 publications
8
104
1
4
Order By: Relevance
“…Using the average height for this sample, an increase of one standard deviation above the mean represented an absolute growth rate of approximately 8.9 cm per year or 0.7 cm per month, which is within the expected range during the adolescent growth spurt . The observations of increased injury incidence and burden around PHV and with absolute monthly growth rates above 0.6 cm per month from other elite sports therefore seem to apply also in athletics, at least for bone and growth plate injuries. While rapid growth in leg length also impacted the overall injury rates, changes in trunk height were not associated with any of the injury categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the average height for this sample, an increase of one standard deviation above the mean represented an absolute growth rate of approximately 8.9 cm per year or 0.7 cm per month, which is within the expected range during the adolescent growth spurt . The observations of increased injury incidence and burden around PHV and with absolute monthly growth rates above 0.6 cm per month from other elite sports therefore seem to apply also in athletics, at least for bone and growth plate injuries. While rapid growth in leg length also impacted the overall injury rates, changes in trunk height were not associated with any of the injury categories.…”
Section: Discussionmentioning
confidence: 99%
“…the peak height velocity (PHV) observed around the age of 11-12 years in girls and 13-14 years in boys, although this varies between individuals. 4 Rapid growth and the period around PHV have been associated with an increased risk of injuries in elite sporting populations, [6][7][8][9][10] and suggested underlying mechanisms include decreased bone mineral density, increased tensile forces on vulnerable muscle attachments, decreased neuromuscular control, and reduced flexibility. 4,7,[11][12][13][14][15][16] Maturation is a more complex concept, referring to the process toward a mature state.…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to these, other factors which may increase the potential for injury in sport should be analyzed. Although there is an increasing interest in the role played by body composition, and anthropometric and growth characteristics as injury risk factors in youth soccer, the research on this topic is still scarce and controversial [ 21 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the player’s age, evaluated as growth and maturation, is an important risk factor, especially in the life period around the peak height velocity (PHV) [ 25 , 26 , 28 , 29 ]. PHV is considered the moment with the largest increase in stature, implying a high growth velocity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Suggested mechanisms for this altered development in adolescents include (1) an underdeveloped ability to estimate an internal model of body orientation [4,9], potentially resulting from a growth spurt [10]; (2) slower movement detection times [11]; (3) mislaid processing mechanisms induced by extensive muscle activation [12]; and (4) the heavy reliance on visual sensory input due to a lack of automatized control strategies [13]. Considering the nature of these causes within the motor control system, it is perhaps unsurprising that a link has been shown between the age of peak height velocity (i.e., the year of the biggest growth in adolescence) and increased injury risk in sport [10,14,15]. Given this relevance, we aim to investigate some of the mechanisms of adolescent awkwardness, with a particular focus on postural movements.…”
Section: Introductionmentioning
confidence: 99%